Unformatted text preview: 5. Let x = the shorter leg 2x – 6 = the longer leg Sentence: The shorter leg is 8 feet and the longer leg is 10 feet. 6. Let x = the shorter leg 2x + 2 = the longer leg (2x + 2) + 1 = the hypotenuse Sentence: The shorter leg is 5 inches, the longer leg is 12 inches, and the hypotenuse is 13 inches. 7. Let x = the shorter leg 3x + 4 = the hypotenuse 3x + 3 = the longer leg Sentence: The shorter leg is 7 feet, the longer leg is 24 feet, and the hypotenuse is 25 feet....
View
Full Document
 Fall '10
 JanetFrewing
 Inch

Click to edit the document details